Dehydration Melting Below the Undersaturated Transition Zone. (3rd February 2020) - Panero, W. R.; Thomas, C.; Myhill, R.; Pigott, J. S.; Raepsaet, C.; Bureau, H.
Abstract: A reflector 70–130 km below the base of the transition zone beneath Tibet is observed in receiver functions and underside seismic reflections, at depths consistent with the transition of garnet to bridgmanite. Contrast in water storage capacity between the minerals of the Earth's transition zone and lower mantle suggests the possibility for dehydration melting at the top of the lower mantle. First‐principles calculations combined with laboratory synthesis experiments constrain the mantle water capacity across the base of the transition zone and into the top of the lower mantle. We interpret the observed seismic signal as consistent with 3–4 vol % hydrous melt resulting from dehydration melting in the garnet to bridgmanite transition. Should seismic signals evident in downwelling region result from water contents representative of upper mantle water globally, this constrains the water stored in nominally anhydrous minerals in the mantle to <30% the mass of the surface oceans. Plain Language Summary: The dynamic mantle circulates material between the upper and lower mantle. At 70–130 km below the upper‐to‐lower mantle boundary, seismic waves indicate an abrupt change in the material properties of the mantle at that depth. We offer a new interpretation of these seismic signals through the calculation of the effects of water on the materials moving from the upper into the lower mantle, which suggests that the decrease in water storage upon pressure‐induced breakdown of garnet can explain the observations through the generation of deep melt. Together with the synthesis of water‐bearing garnet at the relevant pressures, we demonstrate that the synthesis of the observations suggest that the mantle may be significantly limited in water storage, with as little as 30% of the water that is found at the surface of the Earth. Key Points: Seismic reflections at ~750 km depth beneath Tibet are inconsistent with several previously proposed causes for impedance contrast DFT calculation of water partitioning between transition zone and lower mantle minerals accurately predict the water capacity of garnet Sinking transition zone material contains about 300 ppm wt H2 O, leading to dehydration melting upon breakdown of garnet in the lower mantle